Pengaruh Supervisi Akademik dan Motivasi Kerja Guru PAI Terhadap Kinerja Guru PAI Sekolah Dasar Negeri di Kecamatan Cibungbulang Kabupaten Bogor - Mahdalena Juniarsih (Pascasarjana IAI Nasional Laa Roiba Bogor, 2025)
The less than optimal implementation of academic supervision by school principals and the low work motivation of PAI teachers is one of the causes of the low performance of PAI teachers. This research discusses issues including: 1) Is there an influence of academic supervision on the performance of public elementary school PAI teachers in Cibungbulang District, Bogor Regency? 2) Is there an influence of PAI teachers' work motivation on the performance of PAI Elementary School teachers in Cibungbulang District, Bogor Regency? and 3) Is there an influence of academic supervision and work motivation of PAI teachers together on the performance of PAI teachers at Public Elementary Schools in Cibungbulang District, Bogor Regency? The purpose of this research is to determine: 1) The influence of academic supervision on the performance of public elementary school PAI teachers in Cibungbulang District, Bogor Regency. 2) The influence of PAI teachers' work motivation on the performance of PAI Elementary School teachers in Cibungbulang District, Bogor Regency, and 3) The influence of academic supervision and PAI teachers' work motivation together on the performance of PAI teachers at State Elementary Schools in Cibungbulang District, Bogor Regency. This research uses descriptive research with a quantitative approach. Data was collected through questionnaires and processed using statistical calculations with the help of the SPSS version 25 program with a sample of 50 people. The results of the research show: 1) there is an influence of academic supervision on the performance of Public Elementary School PAI teachers in Cibungbulang District, Bogor Regency, amounting to 34.2%, in the moderate/sufficient category and the remaining 65.8% is determined by other factors outside the regression model, 2 ) there is an influence of PAI teacher work motivation on the performance of PAI Elementary School teachers in Cibungbulang District, Bogor Regency, amounting to 37.1%, in the strong/high category and the remaining 62.9% is determined by other factors outside the regression model, 3) there is the influence of supervision The academic and work motivation of PAI teachers together on the performance of Public Elementary School PAI teachers in Cibungbulang District, Bogor Regency is 43.4%, in the strong/high category while the remaining 56.6% is influenced by other variables not examined in the research This. This is proven by the regression results at a significance level of 5%, Fcount = 82.730 is greater than Ftable = 3.114 with a significance value of 0.000 less than 0.05.